At the Syntax-Pragmatics Interface: Acquisition of Turkish Word Order by Turkish-English, Turkish-German and Turkish-Russian Bilingual Children - Çiğdem SAĞIN-ŞİMŞEK; Elena ANTONOVA-ÜNLÜ (Dilbilim Araştırmaları Dergisi, 2021)
The aim of this study is to investigate how syntactic and pragmatic features of Turkish word order are acquired by Turkish-English, Turkish-German and Turkish-Russian bilingual children. The data were collected from Turkish monolingual and bilingual children who were born in England, Germany and Russia and acquired Turkish as their heritage language. The findings of the study reveal that the Turkish monolingual children adopt the use of SOV order as canonical, but they also show sensitivity to the pragmatics of Turkish and use other orders from an early age. Turkish-German, Turkish-English and Turkish-Russian simultaneous bilingual children, on the other hand, showed different patterns of word order acquisition than their Turkish monolingual counterparts.